Novel histological repertoire of crypt-associated anomalies in inflamed colon mucosa - Rubio, Carlos A.; Vieth, Michael; Lang-Schwarz, Corinna (Journal of Clinical Pathology, 2022)
Aims Studying crypt branching in ulcerative colitis (UC) and in infectious colitis (IC), we detected previously unreported crypt-associated anomalies (CAAs). The objective was to describe, illustrate and assess the frequency of CAAs in inflamed colon mucosa in patients with UC and IC. Methods Sections from 100 consecutive biopsies with UC, in 50 with IC and in 27 with UC in remission (UCR) were reviewed. The following CAAs were identified: crypt eosinophilia, intracryptal epithelial hyperplasia, intracryptal epithelial budding, intracryptal supernumerary crypts, intracryptal epithelial bridges, crypt rings in rows and off-centre epithelial budding. Results The frequency of crypts with extensive crypt eosinophilia and with intracryptal epithelial budding was significantly higher in UC than in IC and UCR (p<0.05); the frequency in the remaining histological parameters was similar in UC, IC and UCR. Conclusions CAAs were found interspersed with branching crypts. CAAs persisted in long-lasting UC mucosal inflammation, but declined when the inflammation waned. Since similar anomalies are not present in normal colon mucosa, the results suggest that CAAs had been boosted by the ongoing mucosal inflammation. The development of these previously unreported CAAs in the colon mucosa with inflammation might embody pathological aberrations of cryptogenesis.
CRIS-Team WoS Importer:2022-03-25